Penchant for Print: Media Strategies in Communicating Agricultural Information - Amanda Ruth-McSwain (Journal of Applied Communications, 2008)
The news media provide much of the information the public receives about agriculture and agricultural issues, but they are not the only players in the communication equation. Sources supply the news media with facts and information that eventually direct public thought and opinion about agriculture. Therefore, agricultural communication professionals play a significant role in the dissemination of agricultural information through the news media. In an attempt to better understand the role of agricultural communication professionals, the purpose of this study was to explore their media strategies and choices—specifically their use of different media outlets for their communication efforts. The present applied-exploratory study utilized qualitative methods to gather data from participants. Through 12 in-depth interviews and three online focus groups, a purposive sample of agricultural communication professionals shared their media relations strategies and choices. Overall, the data suggest a preference for working with trade, print media outlets. However, participants also noted that the consolidation and reduction of agricultural media outlets, specifically the farm broadcaster, pose a challenge for the communicator who relies heavily on trade media for their communication needs.
Keywords: Penchant; print; Mewdia; agricultural; information; scientific community; communication